Intensive longitudinal study of newly graduated nurses’ quick returns and self-rated stress - Dahlgren, Anna; Tucker, Philip; Bujacz, Aleksandra; Frögéli, Elin; Rudman, Ann; Gustavsson, Per (Scandinavian Journal of Work, Environment & Health, 2021)
' ' OBJECTIVE ': 'Little is known about the relationship between quick returns (QR) – shift combinations that result in inter-shift rest periods <11 hours) and stress. The current study examined whether variations in the frequency of QR, both between and within individuals, were associated with changes in self-rated stress. ' ' METHODS ': 'A questionnaire was sent weekly to newly graduated nurses during the first 12 weeks of work. Stress was measured with four items from the Stress-Energy Questionnaire on a scale from 1 “not at all” to 5 “very much” [mean 2.65, standard deviation (SD) 1.08]. Shifts worked in the past week were reported and QR were identified by evening-morning shift combinations (mean 0.98, SD 0.90 per week). In total, 350 persons were included in the analysis (3556 observations). Data were analyzed with a multilevel residual dynamic structural equation model (RDSEM) using Bayesian estimation procedures. ' ' RESULTS ': 'There was no between-person effect of QR on stress averaged across measurement occasions (0.181, 95% CI -0.060–0.415). However, there was a small within-person effect of QR (0.031, 95% CI 0.001–0.062), meaning that more QR during a given week, compared to that person’s average, was associated with an increase in their level of stress during that week. ' ' CONCLUSIONS ': 'Nurses were likely to report increased stress during weeks in which they worked more QR. Intervention studies are needed to determine whether the relationship is causal.
Keywords: diary study; longitudinal study; nurse; quick return; recovery; rotating shift; shift work; stress